Investigating the impact of audience response system on student’s performance outcomes - Mantikayan, Jonathan Mamangkian; Abdullah, Lili Marziana; Ayu, Media Anugerah; Abubakar, Adamu; Abdulgani, Montadzah Ambag (IDOSI Publication, 2014)
In this paper Audience Response System (ARS) impact on performance outcomes of secondary school pupils has been studied. Previous research has shown that ARS improves interactive learning and enhances teacher’s ability to understand the degree of how students comprehend his/her teaching. Unfortunately, this might not truly reflect the student’s performance, since the teacher’s concern is to evaluate his/her teaching which might eventually not inculcate the academic values to the students. This paper presents an investigation of the impact of ARS on performance outcomes. The study uses qualitative experiment and evaluates the impact of ARS within some sample of secondary school pupils. An Independent samples T-test was calculated comparing the mean differences of posttest result outcome scores in the treatment group to the mean differences of posttest result score in the control group for each pair of classes taught by the same teacher. No significant difference was found except in class 1 and 2. On further analysis Students utilizing ARS performance has seen to focus on the questions raised by the teacher which improves their memorization ability. Consequently improves their performance outcome.